2015
DOI: 10.4172/1948-5948.1000199
|View full text |Cite
|
Sign up to set email alerts
|

Production, Purification and Characterization of L-Asparaginase from Marine Endophytic Aspergillus sp. ALAA-2000 under Submerged and Solid State Fermentation

Abstract: Among all endophytic fungi recovered from the marine soft sponge Aplysina fistularis, 72.2% were able to produce L-asparaginase. Among all obtained isolates, Aspergillus sp. ALAA-2000, the hyperactive producer for the anticancer agent, L-asparaginase, under submerged fermentation (SMF) and solid state fermentation (SSF) of different agriculture wastes was selected for the optimization of extraction process; optimization of physicochemical parameters, which affecting the production of L-asparaginases in SSF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Currently, L-Asparaginase is industrially produced mainly from prokaryotic microbes such as Escherichia coli and Erwinia chrysanthemi . However, the concomitant presence of the activities of glutaminase and urease means that additional purification steps are required to remove these two enzymes and maintain drug efficacy 9,10 . The presence of glutaminase destroys the necessary glutamine required for the growth of normal cells 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, L-Asparaginase is industrially produced mainly from prokaryotic microbes such as Escherichia coli and Erwinia chrysanthemi . However, the concomitant presence of the activities of glutaminase and urease means that additional purification steps are required to remove these two enzymes and maintain drug efficacy 9,10 . The presence of glutaminase destroys the necessary glutamine required for the growth of normal cells 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Acute Lymphoblastic Leukemia (ALL) is widely distributed among children: 60% at the age of (0-14), 40% to other ages, several studies have been carried out to obtain a safe form of the L-Asparaginase out of fungal sources and they already succeed to get a safe forms of L-Asparaginase (Asha and Pallavi 2012;Abbas Ahmed 2015;Kumar and Sobha 2012). Our results revealed that L-Asparaginase activity were recorded in three native species namely: Fusarium oxysporum, Fusarium solani and Lasiodiplodia theobromae.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic enzymes, it seems out, have a unique ability to facilitate high-affinity interactions with unrelated cancer-related proteins. Endophytic fungi recovered from the marine soft sponge Aplysina fistularis, produce L-asparaginase [57].…”
Section: Anticancer Compoundsmentioning
confidence: 99%